Peran Sekretariat Daerah Dalam Meningkatkan Kinerja Aparatur Kabupaten Indragiri Hulu - Zalvi, Fadlan Rizky; Zainal, Zainal (UIR Press, 2026)
According to Government Regulation Number 17 of 2018 concerning Sub-Districts, Article 10 letter (c) states that the Sub-District Head (Camat) has the authority to coordinate the implementation of public order and security within their jurisdiction. In practice, this coordination includes responsibilities related to regional stability, continuity of inter-agency processes, systematic regulation, unity of action, and achieving common goals. As an extension of the regional government, the Camat plays a strategic role in aligning various community elements, village officials, as well as vertical institutions such as the Indonesian National Armed Forces (TNI) and the National Police (Polri) to address issues related to public order. This study employed a descriptive qualitative method, with data collected through interviews, observation, and documentation involving informants such as the Camat, Head of Public Order (Kasi Trantibum), village heads (Lurah), community leaders, and security personnel. The results showed that the Camat of Pinggir Sub-District has regularly coordinated with related institutions, although several challenges remain. These include a lack of reports from neighborhood units (RT/RW), low community involvement, and weak supervision of social issues such as covert prostitution and alcohol distribution. Additionally, the lack of structured directives to field officers has hindered coordination effectiveness. Therefore, strengthening cross-sectoral communication and actively involving all stakeholders are necessary.